2002
DOI: 10.1128/jvi.76.11.5835-5845.2002
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the Bovine Papillomavirus Origin “Onion Skin”-Type DNA Replication at High E1 Protein Concentrations In Vivo

Abstract: We have studied the replication of plasmids composed of bovine papillomavirus type 1 (BPV1) origin of replication and expression cartridges for viral proteins E1 and E2 in hamster and mouse cells. We found that the replication mode changed dramatically at different expression levels of the E1 protein. At high levels of the E1 protein, overreplication of the origin region of the plasmid was observed. Analysis of the replication products by one-dimensional and two-dimensional gel electrophoresis suggested that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 70 publications
1
21
0
Order By: Relevance
“…5 and 7). Männik et al (44) reported a smear of products, consisting primarily of small fragments shorter than the BPV-1 replicons, when the replicons produced large amounts of BPV-1 E1 protein. These abnormal products were attributed to an onion-skin mode of replication reinitiation from the ori.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 and 7). Männik et al (44) reported a smear of products, consisting primarily of small fragments shorter than the BPV-1 replicons, when the replicons produced large amounts of BPV-1 E1 protein. These abnormal products were attributed to an onion-skin mode of replication reinitiation from the ori.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that elevated levels of an HPV-1 E1 expression vector increased transient ori DNA replication, while increasing levels of an E2 expression vector reduced replication (76). A slight repression of BPV-1 DNA replication by elevated E2 expression was also reported (44).…”
mentioning
confidence: 97%
“…It is possible that E1 unwinds chromosomal DNA, resulting in aberrant replicative intermediates and stalled replication forks and activation of both ATM and ATR pathways. High concentrations of the E1 protein have been shown to promote frequent loading of the helicase at the viral origin, resulting in "onion-skin" replication intermediates (35). In cells with integrated genomes, E1 expression induces amplification of integrated origins, leading to genomic instability and recruitment of the MRN complex, pATM, and pChk2 and phosphorylation of H2AX (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…A model that would fit with the existing data is that E1 needs to be stockpiled for the vegetative part of the viral life cycle and that a high concentration of active E1 is deleterious for cell proliferation. It is well established that high-level expression of BPV E1 can cause problems for the host cell DNA (66). The inactivation of E1 by phosphorylation would allow stockpiling.…”
Section: Discussionmentioning
confidence: 99%